2016
DOI: 10.1371/journal.pone.0145634
|View full text |Cite
|
Sign up to set email alerts
|

Task Shifting the Management of Non-Communicable Diseases to Nurses in Kibera, Kenya: Does It Work?

Abstract: BackgroundIn sub-Saharan Africa there is an increasing need to leverage available health care workers to provide care for non-communicable diseases (NCDs). This study was conducted to evaluate adherence to Médecins Sans Frontières clinical protocols when the care of five stable NCDs (hypertension, diabetes mellitus type 2, epilepsy, asthma, and sickle cell) was shifted from clinical officers to nurses.MethodsDescriptive, retrospective review of routinely collected clinic data from two integrated primary health… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
5

Citation Types

2
92
0
1

Year Published

2018
2018
2024
2024

Publication Types

Select...
7

Relationship

0
7

Authors

Journals

citations
Cited by 76 publications
(95 citation statements)
references
References 15 publications
2
92
0
1
Order By: Relevance
“…Six manuscripts met inclusion criteria, were of average or good quality, were retained for the scoping review, and provided the results of four nurse‐led hypertension intervention studies (Hareri, Abebe, & Asefaw, ; Katende, Groves, & Becker, ; Khabala et al., ; Kumar et al., ; Some et al., ; Vedanthan et al., ). The studies were conducted in outpatient settings in Kenya, Ethiopia, and Uganda.…”
Section: Resultsmentioning
confidence: 99%
See 3 more Smart Citations
“…Six manuscripts met inclusion criteria, were of average or good quality, were retained for the scoping review, and provided the results of four nurse‐led hypertension intervention studies (Hareri, Abebe, & Asefaw, ; Katende, Groves, & Becker, ; Khabala et al., ; Kumar et al., ; Some et al., ; Vedanthan et al., ). The studies were conducted in outpatient settings in Kenya, Ethiopia, and Uganda.…”
Section: Resultsmentioning
confidence: 99%
“…() and Khabala et al. () appeared to have used data from the same set of clinic records because both were implemented in an “urban informal settlement in the Kibera area of Nairobi” (Some et al., ). Each article had 12 authors, eight of whom were authors on both studies.…”
Section: Resultsmentioning
confidence: 99%
See 2 more Smart Citations
“…In a project run by the MSF in Kibera, Kenya, a study by Some et al showed that nurses were able to adhere to protocols for managing stable non-communicable disease (NCD) patients based on a clear standardized protocol [14]. This contributed to a major revision in the Kibera project guidelines which changed the way NCD patients are managed in those facilities.…”
Section: Resultsmentioning
confidence: 99%